Força muscular e composição corporal em idosas : o papel da suplementação da vitamina D - Silva, Patrícia Zambone da (2017)
Organic changes caused by aging cause clinical manifestations in several situations common to elderly patients. Among them, the aging process is associated with a decline in muscle mass and strength. Several factors are involved in this mechanism, among them low D vitamin. OBJECTIVES: verify the effect of D vitamin supplementation on handgrip strength and body composition in elderly women. METHODS: A longitudinal, interventional, uncontrolled study with 54 elderly women at community who do not have severe disabling diseases and do not take D vitamin supplementation. Serum (25 (OH) D) below 30 ng / mL were inclusion criteria in the study. The elderly women performed handgrip strength test (FM), body composition examination by DXA and laboratory tests (parathyroid hormone (PTH), urea (Ur), creatinine (Cr), serum calcium (Ca++) and interleukin-6)). Participants with serum vitamin D levels between 20-29.9 ng/mL were supplemented with 2000 IU per day of cholecalciferol for twelve weeks and those with levels below 20 ng/mL received 10000 IU per day of cholecalciferol for the same period. All had concomitant taking of calcium carbonate 1 g per day. At the end, handgrip strength test, biochemical evaluation and body composition were repeated. For the description of the sample, mean, standard deviation and percentage were used. For data correlation with normal distribution were used Pearson correlation test, and for comparison, Student's T test and for data with non-normal distribution, median, Spearman, Mann-Whitney U and Wilcoxon correlation test. RESULTS: Of the 54 elderly women included in the study, 52 concluded. The mean age was 72 ± 9 years. The mean value before and after supplementation were 25 (OH) D 18.9 ± 6.65 and 38.15 (24.4 – 126.2) (p= 0,000), PTH 87.15 ± 40.08 and 67.55 ± 30.04 (p = 0,000), IL-6 3.6 (1.5 – 15.8) and 2.25 (1.5 – 45.9) (p = 0.04), FM 42.17 ± 14.12 and 42.55 ± 12.78 (p = 0,733), MM 38663 ± 5546 and 38159 ± 6186 (p = 0,132), Ca++ 9,56 ± 0,4 and 9,4 ± 0,35 (p = 0,004). The correlation analysis between variables after the intervention showed an inverse correlation between 25 (OH) D and PTH, FM and IL-6 and between Ca++ and IL-6. Direct correlations occurred between FM and MM and between FM and Ca++. CONCLUSION: Vitamin D supplementation increased serum levels of 25 (OH) D significantly, as well as reduced serum PTH and IL-6 levels, without changes in handgrip strength and total body lean mass.